The influence of nationwide COVID-19 lockdown on the functional impairment and long-term survival of dependent people for carrying out basic activities of daily living in a neighborhood of the city of Madrid, Spain: Orcasitas Cohort Longitudinal Study - Martín Moreno, Vicente; Martínez Sanz, María Inmaculada; Fernández Gallardo, Miriam; Martín Fernández, Amanda; Benítez Calderón, María Palma; Alonso Samperiz, Helena; Pérez Rico, Elena; Calderón Jiménez, Laura; Guerra Maroto, Sara; Sánchez Rodríguez, Elena; Sevillano Fuentes, Eva; Sánchez González, Irene; et al. (Frontiers in Public Health, 2024)
Background: Prolonged confinement can lead to personal deterioration at various levels. We studied this phenomenon during the nationwide COVID-19 lockdown in a functionally dependent population of the Orcasitas neighborhood of Madrid, Spain, by measuring their ability to perform basic activities of daily living and their mortality rate.Methods: A total of 127 patients were included in the Orcasitas cohort. Of this cohort, 78.7% of the patients were female, 21.3% were male, and their mean age was 86 years. All participants had a Barthel index ≤60. Changes from pre-to postconfinement and 3 years afterward were analyzed, and the effect of these changes on survival was assessed (2020)(2021)(2022)(2023).The postconfinement functional assessment showed significant improvement in independence over preconfinement for both the Barthel score (t = -5.823; p <0.001) and the classification level (z = -2.988; p <0.003). This improvement progressively disappeared in the following 3 years, and 40.9% of the patients in this cohort died during this period. These outcomes were associated with the Barthel index (z = -3.646; p <0.001) and the level of dependence (hazard ratio 2,227; CI 1,514-3.276). Higher mortality was observed among men (HR 1,745; CI 1,045-2,915) and people with severe dependence (HR 2.169;. Setting the cutoff point of the Barthel index at 40 provided the best detection of the risk of death associated with dependence.Conclusions: Home confinement and the risk of death due to the COVID-19 pandemic awakened a form of resilience in the face of adversity in the population of functionally dependent adults. The Barthel index is a good predictor of mortality in the medium and long term and is a useful method for detecting populations at risk in health planning. A cutoff score of 40 is useful for this purpose. The noninstitutionalized dependent population is, to a certain extent, an invisible population. Future studies should analyze the causes of the high mortality observed.